Landscape and quaternary environmental change in New Zealand - Shulmeister, James (Atlantis advances in quaternary science, 2017)
This book brings together an overview of the recent geological history, active earth and biological processes and human settlement of New Zealand. Topics covered include the very active neotectonic and volcanic setting. Mountain geomorphic processes are examined and new ideas about landsliding are highlighted. The exceptional sedimentary archives of the Whanganui Basin are also presented. As one of two land masses that extend into the southern mid-latitudes, New Zealand is ideally located to investigate changes in Southern Ocean climate. Related to this, mountain glaciation in New Zealand is a focus in global climate change debates. New Zealand also has a unique biota due to its long isolation and is the last major land mass to be settled by people. Advances in DNA technologies have revolutionised our understanding of the histories and processes involved. The book provides a comprehensive review of existing work and highlights new ideas and major debates across all these fields.